Inverse design in nanophotonics. Issue 11 (November 2018) - Molesky, Sean; Lin, Zin; Piggott, Alexander; Jin, Weiliang; Vucković, Jelena; Rodriguez, Alejandro
Abstract Recent advancements in computational inverse-design approaches — algorithmic techniques for discovering optical structures based on desired functional characteristics — have begun to reshape the landscape of structures available to nanophotonics. Here, we outline a cross-section of key developments in this emerging field of photonic optimization: moving from a recap of foundational results to motivation of applications in nonlinear, topological, near-field and on-chip optics. Starting with a desired optical output it is possible to use computational algorithms to inverse design devices. The approach is reviewed here with an emphasis on nanophotonics.